Pengenalan Dunia Kampus di Sma Negeri 1 Kuala Pembuang Kabupaten Seruyan - Yanis, Muhammad Nazarul; Purnamasari, Tina; Zebua, Dermawan (CV. SINAR HOWUHOWU, 2024)
Campus introduction activities are a form of community service which aims to provide information about the world of higher education and help high school students in determining future career choices. This research was carried out at SMA Negeri 1 Kuala Pembuang, Seruyan Regency, using interactive presentation and discussion methods. The results of the activity showed that students felt more motivated and had a clearer picture of the steps they should take after graduating from high school. Information about various majors and scholarship opportunities is of great interest to students, especially those who have financial constraints. Evaluation shows that this activity succeeded in reducing students' anxiety regarding college entrance selection and provided positive encouragement for them. This campus introduction activity has a significant impact in preparing students to continue their education to a higher level and this service is concrete evidence of the tridharma of higher education, namely Teaching, Research and Community Service.